Management of Intractable Pain in Patients With Implanted Spinal Cord Stimulation Devices During the COVID-19 Pandemic Using a Remote and Wireless Programming System - Lu, Yang; Xie, Duo; Zhang, Xiaolei; Dong, Sheng; Zhang, Huifang; Yu, Beibei; Wang, Guihuai; Wang, James Jin; Li, Luming (Frontiers in Neuroscience, 2020)
As COVID-19 rampages throughout the world with major impacts on the healthcare system, non-emergency medical procedures have nearly come to a halt for appropriate resource reallocation. However, pain never stops, particularly for patients with chronic intractable pain and implanted spinal cord stimulation devices. The isolation required to fight this pandemic makes it impossible for such patients to adjust the parameters or configuration of the device on site. Although telemedicine has shown a great effect in many healthcare scenarios, there have been fewer applications of such technology focusing on the interaction with implanted devices. Here, we introduce the first remote and wireless programming system that enables healthcare providers to perform video-based real-time programming and palliative medicine for pain patients with a spinal cord stimulation implant. During the COVID-19 pandemic from January 23, 2020 (the date of lockdown of Wuhan) to April 30, 2020, 34 sessions of remote programming were conducted with 16 patients. Thirteen of the 16 patients required programming for parameter optimization. Improvement was achieved with programming adjustment in 12 of 13 (92.3%) cases. Eleven of the 16 (68.8%) patients reported that the system was user-friendly and met their needs. Five patients complained of an unstable connection resulting from the low network speed initially, and three of these patients solved this problem. In summary, we demonstrated that a remote wireless programming system can deliver safe and effective programming operations of implantable spinal cord stimulation device, thereby providing palliative care value to the most vulnerable chronic pain patients during a pandemic.